A phenomenological reading of the racial knowledge and identities of student leaders engaged in reconciliation - Buys, Barend Rudolf (University of the Free State, 2017)
𝑬𝒏𝒈𝒍𝒊𝒔𝒉 This study wants to make sense of the lived experiences of student leaders engaged in racial reconciliation at a South African university campus by exploring their struggles with racial knowledge and identity over time. Four students, two male and two female, two black and two white, participated in the study. They were senior student leaders that played a public role in racial reconciliation on campus following a traumatic incident of racial discrimination at Reitz, a men’s residence on campus. The study faced a dearth in current literature on the combined themes of student leadership, racial knowledge and identity, and reconciliation. However, a broad literature review on student engagement, student leadership and student diversity revealed critical themes and gaps relevant to this study in the research on diversity and change in higher education. A framework of concepts was developed to read the narrative data of the study. These included the notions of conscientisation (Freire), racial ignorance (Mills), in-betweenness (Bhabha), transitionality (Winnicott), scapegoating (Girard), nearness (Jansen), embrace (Volf) and bridge-building (Boske). The study uses a phenomenological approach to describe and interpret the life histories of the participating student leaders. I drafted the four racial biographies of the four student leaders in conjunction with the students, which were then analysed for patterns of experiences that reveal shifts in racial knowledge and identity in and across lives. On the one hand, the students reproduced the racial ignorance and the hierarchies of racial distance that marked their lifeworlds. However, on the other hand, the students behaved in alternative ways to the norm of their environments. They built friendship across racial divides and challenged cultural codes and norms. The different and competing realities of racial distance and togetherness reveal a continued struggle between knowledge defined by ignorance and knowledge defined by the transitional context of post-apartheid South Africa. Similarly, their alternative experiences of race in a changing society reveal an alternative racial identity that emerge over time in their lives, an identity of in-betweenness. A synthesis of the emerging themes revealed successive moments of struggle with racial ignorance and alternative knowledge in their lives prior to and on campus, and prior to, during and after Reitz. The students learned to reproduce racial ignorance at school and at home prior to arriving on campus. On campus they faced radical racial distances prior to and immediately after Reitz. But, the trauma of the incident also disrupted the established racial hierarchies of their environment. Thereafter the post-Reitz interventions raised their consciousness about race and racial hierarchies so that ignorance dissipated. At the same time, the transitional nature of their racially integrating schools and local communities compelled new knowledge and identities different to established black and white identities. However, at school and on campus prior to Reitz, the students faced reprisals for their attempts at racial in-betweenness and breaking with racial codes and norms. Reprisals discouraged and cast doubt on new knowledge and identity. They internalised this rejection of their alternative knowledge, but rediscovered its value when the post-Reitz interventions for change embraced in-betweenness and alternative knowledge and identities. Their conscientisation disrupted racial ignorance and brought their in-betweenness and transitional knowledge to the surface. As ignorance dissipated, their new knowledge and in-betweenness were actualised as racial bridge-building. The study defines the students’ struggle with ignorance and transitional knowledge as the struggle of an epistemology of transitionality to emerge in the face of the dominant epistemology of ignorance that marks the post-conflict environment of post-apartheid South Africa. It defines their growing in-betweenness as an emerging ontology of transitionality and uses the notion of bridge-building to define the methodology and praxis of their leadership for racial reconciliation and change. The study contributes to current scholarship on leadership for change in higher education by describing in detail how student leaders experienced change personally and as part of change interventions on a divided university campus. The study provides new ways to make sense of how student leaders who counter-culturally lead reconciliation on campus become leaders for change and the social, cultural and political influences that mediate their transition. The study also contributes potential theoretical readings of transitionality, bridge-building and reprisal as important concepts to theorise leadership for change in higher education. The study recommends further research to test the transferability of the findings of this research.

𝑨𝒇𝒓𝒊𝒌𝒂𝒂𝒏𝒔 Die studie beoog om sin maak van die lewenservarings van studenteleiers wat besig is met rasseversoening op ’n universiteitskampus, deur hulle stryd met rassekennis en -identiteit te ondersoek. Vier studenteleiers, twee mans en twee vroue, waarvan twee swart en twee wit is, het aan die studie deelgeneem. Hulle was senior studenteleiers wat ’n openbare rol gespeel het in rasseversoening op kampus na afloop van ’n traumatiese insident van rassediskriminasie by Reitz, ’n manskoshuis op kampus. Die studie is bemoelik deur die afwesigheid van bestaande literatuur oor die saamgestelde temas van studenteleierskap, rassekennis en -identiteit en versoening.’n Breedvoerige literatuuroorsig oor studentebetrokkenheid, studenteleierskap en studentediversiteit het egter kritiese temas en leemtes toepaslike vir die studie in navorsing oor diversiteit en verandering in hoër onderwys uitgewys. ’n Raamwerk van konsepte is ontwikkel om die narratiewe data van die studie te interpreteer. Dit sluit onder andere die idees van bewuswording (Freire), rasse-onkunde (Mills), tussen-in-wees (Bhabha), transitionaliteit (Winnicott), die sondebok (Girard), nabyheid (Jansen), omarming (Volf) en brugbou (Boske) in. Die studie maak van ’n fenomenologiese benadering gebruik om die lewensgeskiedenisse van die studenteleiers te beskryf en te vertolk. Die navorser en die deelnemers het saam die vier rasse-biografieë opstel, wat ontleed is vir patrone van belewnisse wat skuiwe in rassekennis en -identiteit in en tussen hulle lewens, uitgewys het. Aan die een kant het die studente die rasse-onkunde en rashiërargie wat hulle lewenswêrelde bepaal het, herhaal. Aan die ander kant het die studente op alternatiewe maniere as wat die norm van hulle omgewings is, opgetree deur vriendskappe oor rassegrense heen te bou en kulturele kodes and norms uit te daag. Die verskillende en kompeterende werklikhede van rasse-afstande en -samehorigheid wys ’n voortslepende stryd uit tussen kennis wat deur onkunde gedefinieer word, en kennis wat deur ’n oorgangskonteks gedefinieer word. Net so wys hulle alternatiewe belewenisse van ras in ‘n veranderende samelewing op ’n alternatiewe rasse-identiteit wat met verloop van tyd in hulle lewens na vore tree, ‘n tussen-in identiteit. ’n Sintese van die temas wat na vore tree, wys opeenvolgende oomblikke van ’n stryd met rasse-onkunde en alternatiewe kennis uit in die studente se lewens voor en op kampus, en voor, tydens en na afloop van Reitz. Die vier studenteleiers het voor hulle op kampus aangekom het, op skool en by die huis geleer om rasse-onkunde te herhaal. Op kampus voor en onmiddellik na Reitz het radikale rasseafstande hulle in die gesig gestaar. Maar, die trauma van die insident het ook die gevestigde rassehiërargieë van hulle omgewing omvergewerp. Die intervensies na die Reitz-voorval het hulle bewustheid oor ras en rassehiërargieë verhoog, sodat onkunde minder geword het. Terselfdertyd het die oorgangsdinamieka van rasse-integrasie in die omgewing, hulle skole en hul plaaslike gemeenskappe, nuwe kennis en identiteit aangewakker, wat anders was gevestigde swart en wit identiteite. Die studente het egter op skool en op die kampus voor Reitz vergelding in die gesig gestaar weens hulle pogings om tussen-in rasse te staan en van raskodes en -norme weg te breek. Vergelding het nuwe kennis en identiteit ontwrig en verdag gemaak. Hulle het die verwerping van hulle alternatiewe kennis geïnternaliseer, maar het die waarde daarvan weer ontdek toe die intervensies vir verandering na die Reitz-voorval, hulle tussen-in-wees en alternatiewe kennis en identiteit omarm het. Hulle bewuswording het rasseonkunde omver gegooi en hulle tussen-in-wees en oorgangskennis na die oppervlak gebring. Namate onkunde begin verdwyn het, het hulle nuwe kennis en tussen-in-wees sigbaar geword as brugbouery tussen rasse. Die studie definieer die studenteleiers se stryd met onkunde en oorgangskennis as die stryd van ’n epistemologie van transisionaliteit om na vore te tree in die gesig van ’n oorheersende epistemologie van onkunde wat na apartheid in Suid-Afrika steeds die botoon voer. Dit definieer hulle groeiende tussen-in-wees as ’n groeiende ontologie van transisionaliteit en gebruik die idee van brugbouery om te beskryf hoe hulle dit benader het om, en leiding vir rasseversoening en verandering geneem het. Die studie dra by tot bestaande navorsing oor leierskap vir verandering in hoër onderwys deur te bskryf hoe studenteleiers self verandering as deel van transformasie-intervensies op ’n verdeelde universiteitskampus beleef. Die studie maak op nuwe maniere sin van hoe studenteleiers, wat in weerwil van gevestigde kampuskulture leiding neem met versoening, leiers vir verandering word, asook van die sosiale, kulturele en politieke invloede wat hulle oorgang bemiddel. Die studie voorsien ook ’n moontlike teoretiese uitleg van transisionaliteit, brugbouery en vergelding as belangrike konsepte om teoreties na te dink oor leierskap vir verandering in hoër onderwys. Dit stel verdere navorsing voor om die oordraagbaarheid van die navorsingsbevindings te toets.
Thesis (Ph.D.(Higher Education Studies))--University of the Free State, 2017
Keywords: Bridge-building; Leadership for change; In-betweenness; Racial reconciliation; Student leadership; Transitionality; Transformational leadership -- Study and teaching (Higher) -- South Africa.; Education -- Study and teaching (Higher) -- South Africa.; leierskap vir verandering; tussen-in-wees; rasseversoening; studenteleierskap; transisionaliteit